Multicystic Cerebral Hydatid Cyst: Uncommon Presentation of A Rare Disease - Kaushik, Sil; Sunanadan, Basu; Harsh, Jain; Laxminarayan, Tripathy (Nepal Journal of Neuroscience, 2016)
Hydatid cyst is a common zoonosis, affecting the liver and lungs in the endemic areas. Occasionally it involves the brain. We present a rare case of multicystic cerebral Hydatid cyst present over a long time in an adult patient with some odd radiological features like calcification and discuss the relevant literature. In endemic areas, neurosurgeons must be aware of this entity.Nepal Journal of Neuroscience 12:49-51, 2015